The Impact of Gamification in User Interfaces on User Experience and Retention: An Empirical Study - Widagdo, Pratama; Wandah Wibawanto; Eko Sugiarto (Universitas Negeri Semarang, 2024)
This study investigates the influence of gamification features in UI design on UX and user retention in mobile applications. This experimental research compares two user groups (with and without gamification) using questionnaires that assess UX and user retention, with purposive sampling, and data analysis using descriptive techniques, normality tests, and difference tests. The findings reveal that gamification in mobile app UIs significantly enhances UX and user retention. Key gamification features, such as challenges, achievements, leaderboards, interactive feedback, and social integration, positively impact usability, motivation, satisfaction, and user recommendations. Users in the gamified group reported higher ease of use, engagement, and satisfaction, leading to longer retention periods. This study reveals significant findings that integrating gamification elements into application design can enhance user satisfaction and loyalty, as well as encourage further research in the context of mobile application gamification.